Clinical effectiveness of olaparib monotherapy in germline BRCA-mutated, HER2-negative metastatic breast cancer in a real-world setting: phase IIIb LUCY interim analysis. (July 2021) - Gelmon, Karen A.; Fasching, Peter A.; Couch, Fergus J.; Balmaña, Judith; Delaloge, Suzette; Labidi-Galy, Intidhar; Bennett, James; McCutcheon, Susan; Walker, Graham; O'Shaughnessy, Joyce; ,; Timcheva, Constanta; et al.
Abstract: Background: In the phase III OlympiAD trial, olaparib significantly increased progression-free survival (PFS) compared with chemotherapy of physician's choice in patients with germline BRCA-mutated (gBRCAm), human epidermal growth factor 2 (HER2)-negative metastatic breast cancer (mBC). The phase IIIb LUCY trial assessed the clinical effectiveness of olaparib in similar patients, in a setting reflecting clinical practice. Methods: This open-label, single-arm trial of olaparib (300 mg, twice daily) enrolled patients with BRCAm, HER2-negative mBC who had received taxane and/or anthracycline in the (neo)adjuvant/metastatic setting and not more than two lines of prior chemotherapy for mBC. Patients with hormone receptor–positive mBC had progressed on at least one line of endocrine therapy in an adjuvant/metastatic setting and were unsuitable for further endocrine treatment. This interim analysis was planned after 160 PFS events. Results: Of 563 patients screened, 252 patients with gBRCAm were enrolled and received at least one dose of olaparib. The median investigator-assessed PFS was 8.11 months (95% confidence interval [CI], 6.93–8.67; 166/252 events [65.9% maturity]). The investigator-assessed clinical response rate was 48.6%, and median time to first subsequent treatment or death was 9.66 months (95% CI, 8.67–11.14). The most common treatment-emergent adverse events (TEAEs; >20% patients) were nausea, anaemia, asthenia, vomiting and fatigue. Eleven patients (4.4%) discontinued treatment because of a TEAE. Grade 3 or higher TEAEs occurred in 64 patients (25.4%), including anaemia (33 patients; 13.1%). Conclusion: Olaparib was clinically effective in patients with gBRCAm, HER2-negative mBC with safety outcomes consistent with previous findings. ClinicalTrials.gov identifier: NCT03286842 . Highlights: LUCY was a phase IIIb trial of the PARP inhibitor olaparib. LUCY followed the phase III OlympiAD trial and aimed to reflect clinical practice. Investigator-assessed progression-free survival was 8.11 months (65.9% maturity). Grade ≥3 TEAEs occurred in 64 patients (25.4%), including anaemia in 33 patients. These interim results support previous findings from the OlympiAD trial.